2022
DOI: 10.21037/jgo-22-951
|View full text |Cite
|
Sign up to set email alerts
|

Modification of erythrocytes by internalizing Arg-Gly-Asp (iRGD) in boosting the curative effect of radiotherapy for gastric carcinoma

Abstract: Background: Radiation resistance remains the leading cause of radiotherapy (RT) failure. The development of tumor-specific targeted sensitizers is key to overcoming radiation resistance. Our early data showed that cancer cell penetration was simulated by internalizing arginine-glycine-aspartic acid (iRGD), and the irradiation efficacy was improved. The present study aims to design and fabricate iRGD-modified red blood cell (RBCs) for tumor targeting and RT enhancement, and to evaluate its safety and efficacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As shown in Figure 5 C, the in vitro fluorescence signal of the heart, liver, spleen, lung, kidney and tumour in each group showed that iRGD increased the accumulation of drug in the liver, lung and tumour. The strongest fluorescence intensity was observed in the tumour and lung sites, verifying the tumour-targeting property of iRGD [ 29 ].…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 5 C, the in vitro fluorescence signal of the heart, liver, spleen, lung, kidney and tumour in each group showed that iRGD increased the accumulation of drug in the liver, lung and tumour. The strongest fluorescence intensity was observed in the tumour and lung sites, verifying the tumour-targeting property of iRGD [ 29 ].…”
Section: Resultsmentioning
confidence: 95%
“…To further optimize the tumor‐specificity of NPs, tumor response or tumor cell targeting elements could be introduced, such as IRGD peptides or gelatinase cleavable peptide that reacts to tumor microenvironment as a result of multiple enzymes overexpressed. 35 , 36 Another constraint is its dependence on the existence of MHC class I molecules. The theoretical failure of this approach could occur if tumors experience a decline in MHC class I expression.…”
Section: Discussionmentioning
confidence: 99%
“…As we can see, the delivery system was not specific to tumor region. To further optimize the tumor‐specificity of NPs, tumor response or tumor cell targeting elements could be introduced, such as IRGD peptides or gelatinase cleavable peptide that reacts to tumor microenvironment as a result of multiple enzymes overexpressed 35,36 . Another constraint is its dependence on the existence of MHC class I molecules.…”
Section: Discussionmentioning
confidence: 99%
“…(3) iRGD is linked to the membrane of biological cells, such as T cells (Ding et al, 2019) or red blood cells (RBCs) (C. Zhou et al, 2022), for treatment.…”
Section: Drug Delivery Methods Of Irgdmentioning
confidence: 99%
“…Nanoparticles are often loaded with a variety of chemicals, including chemotherapeutic drugs (Dai et al, 2015; Jin et al, 2016; Song et al, 2012), nucleic acid molecules (Guan et al, 2021; Lo et al, 2018), small‐molecule inhibitors (J. Wang et al, 2016), photosensitizers (Yan et al, 2016; H. Zhang et al, 2022), nanoimaging probes (Yu et al, 2022), and so on. The nucleotide sequence of iRGD is linked to the nucleotide sequence of a protein or peptide via a peptide bond and expressed by an expression system to produce a recombinant antibody (Sha, Li, et al, 2015; Sha, Zou, et al, 2015) or recombinant protein (Lao et al, 2013, 2015; Yang, Yang, et al, 2019), or it can be coupled to a short peptide through a total chemical synthesis (Qifan et al, 2016). iRGD is linked to the membrane of biological cells, such as T cells (Ding et al, 2019) or red blood cells (RBCs) (C. Zhou et al, 2022), for treatment. The sequence of iRGD was inserted into the adenoviral vector and expressed on the surface of the adenovirus, conferring vector targeting (Al‐Zaher et al, 2018; Puig‐Saus et al, 2014). iRGD can be due in part to nanosystems that effectively target the TME (M. Liu et al, 2021; Ray et al, 2019; X. Xu et al, 2016).…”
Section: Drug Delivery Methods Of Irgdmentioning
confidence: 99%